Estrutura etária e reprodução de Marmosops bishopi (Pine, 1981) (Didelphimorphia : Didelphidae) em uma região de ecótono Amazônia-Cerrado - Pereira, Maria Nazaré de Sousa (2021)
Marsupials comprise a group of mammals characterized by short gestation and prolonged lactation periods, with premature newborns attached to the breasts until their complete development. In this study, we investigated the age structure and reproductive indicators in Marmosops bishopi taking into account local seasonal periods. We analyzed 272 specimens (males and females) collected in an Amazonia-Cerrado transition area, for which age class were assigned based on tooth eruption and wear. Tegumentary features of the inguinal region of females were examined in search of external indicators of reproductive condition. Our data indicate that reproduction occurs throughout the year, although there seems to be a preference for the wet season, with a predominance of young specimens of age class 3. Young individuals from age classes 3 and 4 and adults from age classes 6 to 8 occurred in all collection periods. The proportions of males and females were similar in young individuals from age classes 3 and 4, whereas they were greater in adult males from age classes 6 to 9. There were no differences between the number of individuals collected in the dry and wet seasons for young specimens from age class 4 and for adult specimens from age classes 6 to 9, only for young specimens from age class 3 which were more frequently collected during the wet season. The analysis of the inguinal region in females revealed six conditions of reproductive activity, as follows: nonreproductive, pre-reproductive, pre-lactating, lactating, late-lactating and postlactating.